The Influence of Influencer Credibility, Message Personalization, and Brand Trust on Viral Marketing Intention of Local Fashion Brands on Social Media - Hendratni, Tyahya Whisnu; Apramilda, Riesna; Sidjabat, Sonya; Kusnadi, Iwan Henri; Budayanti, Saripermanik; Risdwiyanto, Andriya (Yayasan Gema Bina Nusantara, 2026)
Local fashion companies need to adopt viral marketing techniques because digital market competition requires them to build their brand presence through natural methods. The study tests the effect of three variables which are influencer credibility message personalization and brand trust on local fashion brands' social media viral marketing operations. The study used a quantitative approach which followed an explanatory research design. The researchers conducted a survey to gather data from 210 social media users who followed local fashion brand accounts and engaged with influencer content. The research team applied multiple linear regression analysis to test the data after conducting all necessary validity reliability and classical assumption tests. The findings reveal that users who trust brands from social media platforms together with their personalized messages. The research found that people trusted influencers who displayed credibility which increased their acceptance of messages and content, and personalized messages made users more relevant to the audience while building emotional connections, and brand trust functions as the key element that drives people to support companies. The success of viral marketing in local fashion brands depends on how well they implement influencer communication strategies and personalize content and build trust with customers. The study results create strategic value for local fashion businesses by demonstrating how to develop successful and lasting social media marketing programs.